2020
DOI: 10.1016/j.jobcr.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Histological comparison of DBBM and platelet rich fibrin for guided bone regeneration in a rabbit model

Abstract: To histologically evaluate the use of bovine derived deproteinized xenograft (DBBM), leukocyte and platelet rich fibrin (L-PRF) and the combination of both in Guided Bone Regeneration (GBR) performed in noncritical size defects in rabbit. Methods: A prospective experimental study was performed. Four bone defects in the tibiae of 12 rabbits were made and each of them was filled with DBBM, L-PRF, a combination of DBBM + L-PRF or was left to heal as control site. All defects were covered with a collagen membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We assume that the radiographic defect fill achieved with PRF alone is bone fill, though it remains to be histologically proved. Histologic data on PRF exist for other types of osseous defects, such as experimental [ 74 , 75 ] and human alveolar ridge [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ] defects. The combined PRF/β-TCP graft achieved more new bone formation at twelve weeks than PRF or β-TCP alone, as histologically assessed in experimental tibial defects in pigs [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the radiographic defect fill achieved with PRF alone is bone fill, though it remains to be histologically proved. Histologic data on PRF exist for other types of osseous defects, such as experimental [ 74 , 75 ] and human alveolar ridge [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ] defects. The combined PRF/β-TCP graft achieved more new bone formation at twelve weeks than PRF or β-TCP alone, as histologically assessed in experimental tibial defects in pigs [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined PRF/β-TCP graft achieved more new bone formation at twelve weeks than PRF or β-TCP alone, as histologically assessed in experimental tibial defects in pigs [ 74 ]. L-PRF, bovine derived deproteinized xenograft (DBBM) and combined L-PRF/DBBM covered with collagen membranes had similar outcomes at nine weeks regarding percentage vital bone, percentage connective tissue and percentage remaining graft particles, as histologically assessed in experimental tibial defects in rabbits [ 75 ]. Regarding lateral two-stage sinus augmentation, the predominant human histologic data on the combined PRF/osseous graft, as compared with osseous graft alone, show that the amount of new bone formed is not affected and the bone formation process is accelerated leading to mature bone earlier [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Knapen et al observed that L-PRF did not provide any additional effect on the quantity and quality of bone during guided bone healing over a period of 12 weeks [30]. Frequently, platelet concentrates have been used mixed with bone graft to promote bone regeneration [31]. The growth factors present in APG have been shown to induce bone formation and enhance fibroblast proliferation when mixed with hydroxyapatite [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to certain physical properties meant to maintain space throughout healing and achieve better bone neoformation, grafts in GBR should ideally have as many of the following three biological properties as possible: osteogenicity, osteoinductivity, and osteoconductivity [4]. Xenografts and, more specifically, deproteinized bovine bone minerals, are some of the most widely used types of grafts today because of the successful results they have shown in GBR procedures [5]; they are a good alternative to the gold standard but are primarily and only osteoconductive [6]. This is because, although the organic part is removed to reduce the risk of infection, the inorganic phase-mainly consisting of hydroxyapatite-and its porous architecture are preserved [7].…”
Section: Introductionmentioning
confidence: 99%